Exploring Educators' Commitment to Racial Equity in School Discipline Practice: A Qualitative Study of Critical Incidents. Issue 2 (3rd April 2022) - Bastable, Eoin; McIntosh, Kent; Falcon, Sarah Fairbanks; Meng, Paul
ABSTRACT: As interventions show promise for reducing school discipline disparities, it is important to understand what variables increase educators' commitment toward addressing racial equity in schools. In-depth interviews were conducted with a purposeful sample of 15 educators asked to describe pivotal events that shifted their own or others' active commitment to racial equity in school discipline practice. Analysis of interviews, using an established qualitative methodology, produced 210 observable incidents that were grouped into 22 representative categories. Findings included 14 helping categories, 4 hindering categories, as well as 4 categories describing what could have increased educators' commitment sooner. Implications for practice are discussed in relation to current research, theory, and school consultation models.